Investigation of the Catalytic Activity of Hybrid Decavanadate Materials - DEAK, Noemi; IDBOUMLIK, Meryem; SORAN, Albert; LACHKAR, Mohammed Abdulhakim; EL BALI, Brahim; NEMES, Gabriela (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Three decavanadate (V10O28)6- containing compounds were used to test their catalytic activity in the sulfoxidation reaction of diphenyl sulfide using environmentally friendly conditions (low temperature, non-toxic solvent). The compounds of interest for our study, (NH4)2(H2en)2V10O28·4H2O, (H2en)3V10O28·6H2O and Li2(H2O)10(V10O28)(NH4)4, were evaluated, showing good activity in sulfoxidation reaction and leading to complete conversion of the sulfide even after three runs. The tetraammonium decaaqualithium decavanadate, with the formula Li2(H2O)10(V10O28)(NH4)4 was obtained through a modified literature method and its structure re-determined and investigated, giving similar results as previously described and confirming the structure of the used material.